ANALISIS KEBERHASILAN IMPLEMENTASI ENTERPRISE RESOURCE PLANNING - Rika A Susanti; Dini Wahjoe Hapsari (JAF (Journal of Accounting and Finance), 2017)
This study was designed to analyze the effect of top management support, business process reengineering, effective project management, change management, training and education to the successful implementation of ERP in PT. Telekomunikasi Indonesia Tbk Japati, Bandung. This research method using regression analysis with a survey technique in which the population of this study is on the Enterprise & Analytic Platform Development. Research hypothesis testing is done using the F test and t test and descriptive analysis. The data were obtained using a questionnaire research instruments that contain a list of statements to measure the respondents to the study variables. The results from this research indicate that simultaneously successful implementation of ERP influenced by critical success factor with a value of r-square 79% and partially variable top management support, business process reengineering, effectiveness project management not associated with successful implementation of ERP and variable change management, training and education are significantly associated with successful implementation of ERP. Based on the research results, to improve the success of ERP implementation, Enterprise & Analytic Platform Development at Telkom should conduct change management and improving training and education to employees to enhance the ability of employees to use the ERP system